1999
DOI: 10.1021/jp9915836
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Dynamics in Irreversible Nonequilibrium Environments. 3. Temperature-Ramped Chemical Kinetics

Abstract: A generalization of the generalized Langevin equation (stochastic dynamics) is introduced in order to model chemical reactions which take place in environments with both density and temperature variations. This phenomenological constructionsgiven the name irreversible generalized Langevin equation (iGLE)sensures that both the bath and its response to the chosen coordinates of the projected systems are characterized by the same imposed temperature profile. As in the earlier construction, the present generalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…For the last decade there have been several attempts at establishing the nonstationary representation termed as the irreversible generalized Langevin equation (iGLE). [25][26][27][28][29][30][31][32][33][34] In particular, the idea of generalized friction kernel 28, 34 dependent on both the time values at the past and the present was proposed. As the (nonstationary) bath relaxes to the equilibrium state as time proceeds, the friction kernel is shown to converge to the usual equilibrium one, which depends only on the time difference.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the last decade there have been several attempts at establishing the nonstationary representation termed as the irreversible generalized Langevin equation (iGLE). [25][26][27][28][29][30][31][32][33][34] In particular, the idea of generalized friction kernel 28, 34 dependent on both the time values at the past and the present was proposed. As the (nonstationary) bath relaxes to the equilibrium state as time proceeds, the friction kernel is shown to converge to the usual equilibrium one, which depends only on the time difference.…”
Section: Introductionmentioning
confidence: 99%
“…As the (nonstationary) bath relaxes to the equilibrium state as time proceeds, the friction kernel is shown to converge to the usual equilibrium one, which depends only on the time difference. The generalization of the fluctuation-dissipation theorem was also proposed: the autocorrelation of the random force averaged over a given distribution of the initial condition of the bath dof corresponds to the generalized time-dependent friction kernel [28][29][30][31][32][33][34] or with an exponentially dumping correction term, [25][26][27] depending on how to formulate the iGLE. The iGLE can be applied not only to phenomena subject to an outside force that changes the solvent response, 28 but also to systems whose nonstationarity is induced by the dynamics of the system itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3,4,5,6,7,8,9,10,11,12,13,14,15 In recent work, 16,17,18,19,20 it was suggested that in many instances, the environment is not stationary, and as such a nonstationary version of the GLE would be desirable. In principle, it is easy to write a nonstationary GLE aṡ…”
Section: Introductionmentioning
confidence: 99%
“…(1) and as such is an example of nonstationary stochastic dynamics. In recent work, 16,17,18,19,20 a generalization of this model was developed which includes arbitrary nonstationary changes in the strength of the friction, but like the xGLE model does not include changes in the response time. As such it is not quite the ultimately desired nonstationary GLE.…”
Section: Introductionmentioning
confidence: 99%